Attention bias modification augments cognitive–behavioral group therapy for social anxiety disorder: a randomized controlled trial. Issue 13 (20th December 2017) - Lazarov, Amit; Marom, Sofi; Yahalom, Naomi; Pine, Daniel S.; Hermesh, Haggai; Bar-Haim, Yair
Abstract: Background: Cognitive–behavioral group therapy (CBGT) is a first-line treatment for social anxiety disorder (SAD). However, since many patients remain symptomatic post-treatment, there is a need for augmenting procedures. This randomized controlled trial (RCT) examined the potential augmentation effect of attention bias modification (ABM) for CBGT. Methods: Fifty patients with SAD from three therapy groups were randomized to receive an 18-week standard CBGT with either ABM designed to shift attention away from threat (CBGT + ABM), or a placebo protocol not designed to modify threat-related attention (CBGT + placebo). Therapy groups took place in a large mental health center. Clinician and self-report measures of social anxiety and depression were acquired pre-treatment, post-treatment, and at 3-month follow-up. Attention bias was assessed at pre- and post-treatment. Results: Patients randomized to the CBGT + ABM group, relative to those randomized to the CBGT + placebo group, showed greater reductions in clinician-rated SAD symptoms post-treatment, with effects maintained at 3-month follow-up. Group differences were not evident for self-report or attention-bias measures, with similar reductions in both groups. Finally, reduction in attention bias did not mediate the association between group and reduction in Liebowitz Social Anxiety Scale Structured Interview (LSAS) scores. Conclusions: This is the first RCT to examine the possible augmenting effect of ABM added to group-based cognitive–behavioral therapy for adult SAD. Training patients' attention away from threat might augment the treatment response to standard CBGT in SAD, a possibility that could be further evaluated in large-scale RCTs.